Supply Chain Management : Practice, Performance and Its Impact on Business Performance - Muhammad, Hashim (2004)
The main objective of this research to determine the level of SCM practices adoption, performance and the impacts it has on manufacturing firms business performance. The instrument used in this study is adopted from Li et al. (2002a, 2002b). In this study, three variables that being used are: SCM Practices, SCM Performance and Business Performance. Previous literature related to SCM are reviewed. Set of questionnaires have been sent to 162 firms located in Kedah, Penang and Perlis, and yielded 33 responses. Rigorous statistical methods were used to analyse the data. The methods used are descriptive analysis, cross-tab analysis, correlation analysis, regression analysis and U-test. The research found that implementation and performance of SCM among manufacturing firms are still at the moderate level. The research findings support the notion that higher levels SCM practice will lead to improved SCM performance. However, the finding reveals that higher level of SCM performance will not lead to better business performance. The research also found that there is no difference in SCM practices and performance between manufacturing firms with special program to embark SCM and without it. Directions and recommendations are discussed on how manufacturing firm to realize the benefits of SCM and to implement it effectively.